Informational Value of Proadrenomedullin Blood Levels in Patients with Septic Shock, Once Measured Upon Admission to ICU - V. А. Rudnov; А. V. Moldovanov; M. N. Аstafieva; E. Yu. Perevalova; V. А. Bagin; S. M. Rozanova (Вестник анестезиологии и реаниматологии)
The objective: to assess the information value of proadrenomedullin (PAM), once measured upon admission to ICU in predicting mortality and differential diagnosis of septic and hypovolemic shock.Subjects and Methods. A prospective cohort retrospective study was carried out. 134 patients in a state of shock were included in the study. Of these, 125 patients had septic shock; 9 ‒ hypovolemic one. The diagnosis of septic shock was established according to the Sepsis-3 criteria. To compare hypovolemic and septic shock, blood levels of proadrenomedullin (PAM), procalcitonin (PCT) and lactate were tested in 9 patients with obvious hypovolemic shock. Samples (venous blood) were collected within 24 hours from the moment the vasopressors began to be used in ICU or by the ambulance team (EMS).Results. The ROC analysis showed comparable predictive value with APACHE II, SOFA and lactate scales in patients with septic shock with cut-off > 4.23 nmol/L. The range of PAM values in patients with septic shock was Me 4.56 (2.9‒6.7) in patients with hypovolemic shock – Me 0.6 (0.1‒1.4).Conclusion. Proadrenomedullin can be used for differential diagnosis of septic shock and hypovolemic shock. Blood levels greater than 2.9 nmol/L are of absolute value for the diagnosis of septic shock. Procalcitonin is inferior to PAM within the range of 1.0–6.45 ng/ml. PAM unlike SCT is a statistically significant predictor of global outcome in septic shock along with lactate and scales. But such scales as SOFA and ARACНE-II are more laborious in comparison with testing proadrenomedullin blood level.